Management accounting innovations and institutionalization process: A case study in the public sector - Pimentel, L.; Conceição, A. (13th ENROAC Conference, 2023)
Objectives: Drawing on the institutional relational dynamics model of Dillard et al. (2004), and intending to close a gap found in literature, the main objective of this investigation is the study of micro processes related to how organizations and actors interact with external pressures. The scope of this paper is the organizational context of a specific Portuguese government agency (IGFSS), where a deep management change process occurred and innovative management accounting frameworks were implemented. Institutional theory was adopted to support the investigation, particularly literature on the interaction between the macro-level (the global) and the micro-level (the local) Data and Methods: A retrospective and in-depth longitudinal case study was conducted at the organization, to tackle the gap found in literature. To support the study, forty-seven interviews were conducted and extensive documentation was analysed for the organization. The research questions posed were thus: i) how did IGFSS react to the external pressures and trends for changing its management accounting systems (MAS)?; and ii) how can be explained the dynamics of MAS change in IGFSS? The case study carried out is mainly explanatory. 2 Results: Dillard et al. (2004) model proved to fit, in general, in the institutionalization process that occurred in the organization, and explains some of the reasons for the observed practices. Pressures and trends and some innovative frameworks associated with the upper levels (environment) of the field site were identified. Findings indicate internal dynamics of change which are not explicitly addressed in that model (a ‘black box’). Borrowing mainly from the contributions of Cruz et al. (2009, 2011), and Lounsbury (2001, 2008), those internal dynamics were translated into practice variation, visualized in performance management and quality management. Moreover, practice variation can also be analyzed within the scope of the different levels of performance management and quality management which were implemented in IGFSS. Conclusions: The introduction of practice variation, as a complement of Dillard et al. (2004) model and of Hopper and Major (2007) revised model, is the main contribution of the investigation. Indeed, the existing of conflict logics induced practice variation. Additionally, Dillard et al. (2004) model proved to be an important model to explain observed practices related to institutionalization processes in organizations.